Strategi Meningkatkan Kepuasan Kerja Pegawai (Studi pada Organisasi Publik) - Mohamad Afan Suyanto (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This paper aims to determine the effect of competence and employee placement on job satisfaction at the Gorontalo Regency Agriculture Office. The problem is focused on whether competence and employee placement have an effect on job satisfaction at the Gorontalo Regency Agriculture Office. To approach this problem, the opinion of Wibowo (2014) on competence, Rivai & Sagala (2011) on job placement and Suyanto, Paramata, & Abdul, 2019 on job satisfaction are used. Data were collected through the census method using the entire population as a sample in this study totaling 40 respondents. The data analysis method used is quantitative analysis using multiple linear regression analysis. With the help of the Statistical Product and Service Solution (SPSS) program. This study concludes that (1) the test results on the competence variable have a positive and insignificant effect on job satisfaction at the agricultural office (2) the test results on the employee placement variable have a positive and significant effect on job satisfaction at the agricultural office. Based on the results of this study, it was formulated a way to improve the work of employees in public organizations by increasing the competencies possessed by employees and placing employees on their passion.